Implementasi Logika Sistem Smart Door Lock Berbasis Arduino dengan Kontrol Aplikasi Mobile untuk Peningkatan Keamanan menggunakan metode Fuzzy Sugeno - Zahidah Hanum Al-Zahra; Fauzia Eka Mardiana; Moch Yasin (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
The development of technology in Internet of Things (IoT) devices has driven global innovation in home security systems, particularly in door lock mechanisms, as conventional locks are prone to being lost or duplicated. Most previous studies we reviewed designed home security lock systems using Raspberry Pi, ESP32, fingerprint sensors, RFID, and third-party platforms. Existing smart locks often fall short when it comes to affordability, user interface flexibility, and the quality of their mobile apps. Our project addresses these shortcomings by developing a new smart door lock prototype. The system consists of an ESP32-based unit controlled via a purpose-built mobile application. The real brains of the operation is the Fuzzy Sugeno method, which handles all the decision-making. The ESP32 is at the core of our system, responsible for interpreting instructions from the mobile application. We evaluated its effectiveness by testing several critical parameters, including access time, the system's response to failed attempts, and the validity of user credentials. The test results were a success: the system consistently and correctly identified the lock's status. Overall, this project delivered an efficient and low-cost security system that is easy to control, offering a practical new option for today's IoT-based smart homes.